Introduction to Complex Impedance Spectroscopy: An Overview - Madhava Rao, Mora Veera (Research Trends and Challenges in Physical Science Vol. 2, 2021)
Impedance spectroscopy is a relatively new and powerful method of investigating electrical and dielectric properties of materials and their interfaces with electronically conducting electrodes. The complex impedance data analysis can yield near-perfect estimates of bulk conductivity of the materials and polarization effects. This book chapter provides a practical guideline to students to calculate impedance spectroscopy which will be applied to investigate electrochemical systems.